Strategic Information System and Interoganitation Planning - Widiadnyana, Putu; Wijaya, Ari Putra; Manuaba, Ida Bagus (International Journal of Engineering and Emerging Technology; Vol 1 No 1 (2016): July - December)
In the business development within an organization can’t be separated from the role of information systems and also support from other organizations. It needs a strategic plan to support the vision, mission and company objectives. Strategy that developed need to be supported with information that can support organization system which helps in the enterprise information system. With the existence of strategic information system and system interorganizational the company is able to build relationships with supplier and distributors to maximize product value and improve product competitiveness